Peripheral retinal changes in highly myopic young Asian eyes. Issue 7 (25th March 2018) - Chen, David Z.; Koh, Victor; Tan, Marcus; Tan, Colin S.; Nah, Gerard; Shen, Liang; Bhargava, Mayuri; Cheng, Ching‐Yu; Zhao, Paul; Wong, Tien Yin; Saw, Seang‐Mei
Abstract: Purpose: To determine the type and prevalence of peripheral retinal changes and its relationship with axial length (AL) in a population of young Asian adult males. Methods: This was a cross‐sectional study of male subjects aged between 19 and 25 years old. High myopes [spherical equivalent refraction, (SER) < −6.00 D] were recruited and underwent further ocular investigations including dilated retinal photography and binocular indirect ophthalmoscopy by two trained ophthalmologists. The frequency of peripheral retinal changes within high myopes was correlated with axial length and also compared with a group of emmetropes (SER between −0.50 D and +1.00 D). Results: A total of 593 high myopes and 156 emmetropes were recruited. White without pressure (WWOP; n  = 458, 46.5%) and lattice degeneration (LD; n  = 109, 14.6%) were the commonest findings, and their prevalence was significantly higher among high myopes (LD, 16.9% versus 5.8%; WWOP, 57.2% versus 5.8%; both p < 0.001). Among high myopes, temporal LD was more common (71%) and 35% had more than one area in the same eye. Increasing AL was associated with LD (odds ratio 1.28, p = 0.01) and retinal holes (odd's ratio 1.44, p = 0.02) on multivariate analysis. Conclusion: White without pressure (WWOP) and LD were the commonest peripheral retinal changes. One‐third of high myopes with LD had more than one area in the same eye. Increasing AL was associated with LD and retinal holes. Studies in older adults should be conducted to develop clinical guidelines for the management of high myopes.